2010
DOI: 10.1158/1078-0432.ccr-09-2282
|View full text |Cite
|
Sign up to set email alerts
|

Phase II, Randomized Trial to Compare Anastrozole Combined with Gefitinib or Placebo in Postmenopausal Women with Hormone Receptor–Positive Metastatic Breast Cancer

Abstract: Purpose: This phase II randomized trial evaluated the efficacy and tolerability of anastrozole combined with gefitinib or anastrozole with placebo in women with hormone receptor-positive metastatic breast cancer (MBC).Experimental Design: Postmenopausal women with hormone receptor-positive measurable or evaluable MBC who had not received prior endocrine therapy for this disease stage or who developed metastatic disease during/after adjuvant tamoxifen were eligible. The primary response variable was progression… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(95 citation statements)
references
References 19 publications
3
89
0
3
Order By: Relevance
“…Some data however from a recently reported study of anastrozole plus or minus gefitinib in advanced disease showed greater promise [15]. This study reported a prolongation of progression free survival from a…”
Section: From Her2 or Egf Receptor (Egfr) Pre-clinical Studies With mentioning
confidence: 95%
“…Some data however from a recently reported study of anastrozole plus or minus gefitinib in advanced disease showed greater promise [15]. This study reported a prolongation of progression free survival from a…”
Section: From Her2 or Egf Receptor (Egfr) Pre-clinical Studies With mentioning
confidence: 95%
“…Polychronis et al [22] studied patients with ER ϩ EGFR ϩ primary breast cancer in the preoperative setting; patients were exposed for 4 -6 weeks to gefitinib monotherapy or combination therapy with anastrozole. Both monotherapy and combination therapy were associated with a notable reduction in tumor size and Ki-67 activity [19]. Based on these sets of data, gefitinib seems to be promising in patients with these tumors, but clinical trials are warranted for the use of gefitinib with anastrozole, specifically in the ER ϩ PR Ϫ subset of patients.…”
Section: Alternative Treatment Strategiesmentioning
confidence: 98%
“…Clinically, it is crucial to block this crosstalk by inhibiting signaling networks to achieve optimal therapeutic activity [3]. This process can be delayed or reversed by inhibiting EGFR and ER signaling by simultaneous treatment with growth factor pathway inhibitors with endocrine therapy [19]. The strategies to inhibit growth factor signaling include mTOR inhibitors (everolimus, temsirolimus), PI3K inhibitors, tyrosine kinase inhibitors, IGF receptor inhibitors, and EGFR inhibitors [20].…”
Section: Alternative Treatment Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many patients with initial response to et will acquire secondary resistance, commonly defined as disease progression more than 6 months after et initiation 11,12 . While there appears to be clinical benefit in combining therapies targeted to the human epidermal growth factor receptor 2 (her2) with et in her2-positive (her2+) abc 13,14 , attempts at combining other receptor tyrosine kinase inhibitors with et in the her2-negative (her2-) setting have met with limited success [14][15][16] , highlighting an unmet clinical need in this population.…”
Section: Introductionmentioning
confidence: 99%